THE STUDY OF BILINGUAL DYSLEXIC CHILDREN LEARNING HINDI AND ENGLISH AT MORPHO - PHONOLOGICAL LEVEL - Das, Dr. Mamta (IJRDO - Journal of Social Science and Humanities Research, 2022)
This research is a study of 20 bilingual dyslexic children learning Hindi and English in the schools of Delhi. A comparative study on was carried out among 20 dyslexic children and 20 chronologically age (CA) matched controls in the age group of 6-15 years both in Hindi and English language separately. The focus of this research is to understand the lexical usage and development by examining the various morpho-phonological characteristics that are unique to dyslexic children. The effect of orthography was also observed to understand the cognitive process in reading and writing in the two different orthographies.